PLANNING OF SUSTAINABLE RIVERSIDE AGROFORESTRY IN THE UPSTREAM AREA OF CITANDUY WATERSHED (CIMUNTUR RIVER), CIAMIS REGENCY, WEST JAVA - M. R. J. F., Fardan
The Citanduy Watershed in West Java is in critical condition. Despite its importance as a vital livelihood resource for local communities, particularly through agroforestry practices, the watershed faces challenges. Agroforestry in the Citanduy Watershed remains suboptimal, reflected in the inadequate implementation of silvicultural systems and limited economic benefits. This study aims to: 1) identify existing planting patterns and silvicultural systems used by communities, 2) estimate stand potential based on growth rates, timber yield, total potential income, and land expectation value (LEV), and 3) quantify the contribution of agroforestry profits to total household income. Data was collected through purposive sampling, using stand inventories and questionnaires administered through interviews. Data analysis employed descriptive and quantitative methods, including interpretations of calculated parameters supported by Pearson and Spearman correlation tests. Results revealed nine distinct agroforestry patterns in the Upper Citanduy Watershed (Cimuntur River). The average silvicultural intensity value was 11.5, with the highest value (15) observed in pattern 9 (A7F2D35). The average stand growth rate for timber trees was 6.31 m3/ha/year, reaching its peak in pattern 2 (A5F1D10) at 15.11 m3/ha/year. The average cumulative timber harvest volume was 169.48 m3/ha/rotation, with the highest value (284.94 m3/ha/rotation) in pattern 7 (A5F5D35). The average total potential income was Rp9.10 billion (Indonesian Rupiah), peaking at Rp24.4 billion in pattern 9 (A7F2D35). The average land expectation value (LEV) was Rp12.04 billion, with the highest value of Rp22.59 billion observed in pattern 8 (A8F2D10). Notably, the average contribution of agroforestry profits to total household income was 84.59%, reaching its maximum at 98.04% in pattern 2 (A5F1D10).